A modified switching procedure from temporary to tunneled central venous dialysis catheters - Eberhard, Johannes; Bedau, Constantin; Chapple, Andrew Genius; Klein, Julia; Reißfelder, Christoph; Kälsch, Anna-Isabelle; Gerken, Andreas; Zach, Sebastian; Schwenke, Kay (Journal of Clinical Medicine, 2024)
Background: Tunneled central venous catheters are commonly used for dialysis in patients without a functional permanent vascular access. In an emergent setting, a non-tunneled, temporary central venous catheter is often placed for immediate dialysis. The most critical step in the catheter insertion is venipuncture, which is often a major cause for longer intervention times and procedure-related adverse events. To avoid this critical step when placing a more permanent tunneled catheter, an exchange over a previously placed temporary one can be considered. In this paper, we present a modified switching approach with a separate access site. Methods: In this retrospective analysis of a prospective database, we examined whether this modified technique is non-inferior to a de novo application. Therefore, we included all 396 patients who received their first tunneled dialysis catheter at our site from March 2018 to March 2023. Out of these, 143 patients received the modified approach and 253 the standard de novo ultrasound-guided puncture and insertion. Then, the outcomes of the two groups, including adverse events and infections, were compared by nonparametric tests and multivariable logistic regression. Results: In both groups, the implantations were 100% successful. Catheter explantation due to infection according to CDC criteria was necessary in 18 cases, with no difference between the groups (5.0% vs. 4.4% p = 0.80). The infection rate per 100 days was 0.113 vs. 0.106 in the control group, with a comparable spectrum of bacteria. A total of 12 catheters (3 vs. 9) had to be removed due to a periinterventional complication. An early-onset infection was the reason in two cases (1.3%) in the study group and five in the control group (1.9%). A total misplacement of the catheter occurred in two cases only in the control group. After adjustment for potential confounders via multivariable logistic regression there was not a significant difference in the complication rate (adjusted odds ratio, aOR = 0.53, 95% CI = 0.14-2.03, p = 0.351) but an estimated decreased risk overall based on the average treatment effect of -1.7% in favor of the study group. Conclusions: The present study shows that a catheter exchange leads to no more infections than a de novo placement; hence, it is a feasible method. Moreover, misplacements and control chest X-rays to exclude pneumothorax after venipuncture were completely avoided by exchanging. This approach yields a much lower infection rate than previous reports: 1.3% compared to 2.7% in all existing aggregated studies. The presented approach seems to be superior to existing switching methods. Overall, an exchange can also help to preserve veins for future access, since the same jugular vein is used.